Oral health before and during the COVID-19 pandemic at the primary care at the Ipatinga in state of Minas Gerais (Research, Society and Development, 2022)
In UHS, primary health care (PHC) is the main gateway to health services and actions with the main objective of offering health promotion and disease prevention, at individual or collective level. This study aims to analyze the use of oral health in primary care in the municipality of Ipatinga before and during the pandemic of COVID-19. Through secondary data obtained from the health information system for primary care (SISAB). A descriptive analysis was performed in order to compare the curative and preventive procedures that occurred in the years 2019 and 2020. The results showed that in both years analyzed the amount of preventive and health educational procedures was greater than curative procedures. The procedures performed in 2020 were less than those performed in 2019. The pandemic of COVID-19 generated direct impacts in the health area which may justify the expressive decrease in the performance of procedures. It is evident that, in the PHC of the municipality of Ipatinga, there is a prevalence of preventive procedures over curative ones. However, despite the reduction in procedures during the pandemic of COVID-19, the percentage of preventive care continued to outnumber curative care.